Fathoming the warm waters: The Russian Mediterranean adventure in the age of Napoleonic wars, 1798-1807 - Morkva, Valeriy (Cappadocia Journal of Area Studies, 2022)
The French advances in Europe during the age of the Napoleonic wars, as well as Napoleon Bonaparte’s Egyptian expedition, paved the way for a previously unthinkable alliance between the Russian and Ottoman empires. Both militarily and ideologically, France had become a threat to both monarchies, so in late 1798, for different reasons, the interests of both monarchies coincided. As a result of the defensive alliance between St. Petersburg and the Sublime Porte, the Russian fleet was granted passage through the Black Sea Straits, and the joint Russian-Ottoman naval fleet launched a military expedition against the French in the Mediterranean. The Ottoman-Russian forces subsequently ousted the French from the Ionian Archipelago off the west coast of continental Greece, and Russia gained de facto control over the Ionian Islands and established a naval base in the Adriatic Sea, where it stayed until 1807. The present article draws from a variety of published and unpublished primary sources to analyse and briefly outline the circumstances behind the creation of the Septinsular Republic on the Ionian Islands and the short-lived Russian residency in the Central Mediterranean during the discussed period.